Research on value co-creation mechanism of platform enterprises in digital innovation ecosystem: A case study on Haier HOPE platform in China - Li, Yuhua; Fu, Kaiwen; Gong, Xiheng; Xiang, Ziwei; Zhang, Jingyi; Liao, Chengjun (Frontiers in Psychology, 2022)
Digital technology has given the innovation subject a new way of value creation, expanded the existing innovation ecosystem theory, and triggered scholars' in-depth thinking on the digital innovation ecosystem. Based on the event system theory and taking Haier’s hope platform as a vertical case study, this paper deeply explores the research mechanism of value creation of platform enterprises in the digital innovation ecosystem, and reveals the role and impact of digital innovation ability, openness, and business innovation model on the process of co-creation. The research results show that: that in the open connection stage, the platform solves the problem of weakening the advantages of the platform, and improves the innovation efficiency of enterprises by continuously improving the digital innovation ability; in the interactive and iterative stage, the platform carries out open innovation, breaks through the difficulties of platform expansion, and realizes the benign expansion of the platform. In the co-creation stage, the user experience is blocked, and the platform adopts the platform community business model to connect the user relationship and improve the user experience. In the digital innovation ecosystem, platform enterprises gradually form self-organization and self-circulation value co-creation through internal self-construction and external cooperation, and form a data-driven co-creation model.